ИЧКИ ИШЛАР ХОДИМЛАРИНИНГ БИЛИШГА БЎЛГАН ҚИЗИҚИШИНИ ОРТТИРИШ ОМИЛЛАРИ - Гулямова, Г.Б. (SCIENCE and SOCIETY, 2023)
In this article, the importance of scientific and creative competition in increasing the interest of internal affairs officers in learning, sharpening in the course of the lesson, scientific circle meetings, scientific-theoretical, scientific-practical gatherings and examinations and olympiads of different levels and directions, modernity and demandingness in internal affairs officers, it is said that the spirit of creativity should be more inculcated.
Keywords: scientific potential; national pride; pride; international audiences; internal affairs personnel; integration; military education; military education field; production; intellectual potential; military personnel